Cortical Neurons form a Functional Neuronal Network in a 3D Printed Reinforced Matrix - Janzen, Dieter; Bakirci, Ezgi; Wieland, Annalena; Martin, Corinna; Dalton, Paul D.; Villmann, Carmen (Advanced Healthcare Materials, 2020)
Impairments in neuronal circuits underly multiple neurodevelopmental and neurodegenerative disorders. 3D cell culture models enhance the complexity of in vitro systems and provide a microenvironment closer to the native situation than with 2D cultures. Such novel model systems will allow the assessment of neuronal network formation and their dysfunction under disease conditions. Here, mouse cortical neurons are cultured from embryonic day E17 within in a fiber-reinforced matrix. A soft Matrigel with a shear modulus of 31 ± 5.6 Pa is reinforced with scaffolds created by melt electrowriting, improving its mechanical properties and facilitating the handling. Cortical neurons display enhance cell viability and the neuronal network maturation in 3D, estimated by staining of dendrites and synapses over 21 days in vitro, is faster in 3D compared to 2D cultures. Using functional readouts with electrophysiological recordings, different firing patterns of action potentials are observed, which are absent in the presence of the sodium channel blocker, tetrodotoxin. Voltage-gated sodium currents display a current–voltage relationship with a maximum peak current at −25 mV. With its high customizability in terms of scaffold reinforcement and soft matrix formulation, this approach represents a new tool to study neuronal networks in 3D under normal and, potentially, disease conditions.
CRIS-Team Scopus Importer:2020-03-27
Keywords: 3D electrophysiology; 3D neuronal networks; cortical neurons; melt electrowriting